How Do Small and Medium-Sized Enterprises Create Value Through the Integrated Reporting Framework? Empirical Study on Integrity and Driving Factors - Furtuna, Ozlem Kutlu; Uykulu, Asiye Zeynep (SAGE PUBLICATIONS INC, 2025)
This paper investigates the levels of Integrated Reporting (IR) content elements alignment in the context of Borsa Istanbul (BIST) Small and Medium-sized Enterprise (SME) Industrial Index, the integrity of the content elements, and the financial factors related to company size, company profitability, leverage and market performance that influence IR disclosure. This study also aims to demonstrate the current situation in which integrated thinking is applied in SMEs and how they can create value for all stakeholders. The population of the paper comprises all firms included in the BIST SME Industrial Index. As of 2022, 46 firms are listed in this index and whose data was fully accessible in 2022 were selected as the sample for the study. This study determines the level of IR content elements alignment scores for Turkish-listed SMEs using the content analysis method. Pearson correlation analysis was utilized between the principles to analyze the degree of integrity. A regression analysis was performed to understand whether the financial factors influence the alignment of the IR content elements. The comprehensive results show that the BIST SME Industrial Index firms do not fully meet the content elements of the International Integrated Reporting Council (IIRC) Framework, however, has an effort to disclose information about the content elements in terms of organizational overview, external environment, and business models. The coal and lignite mining industry has the highest average alignment with the IR content elements, which is consistent with the view that the IR voluntary adoption should be adopted by the most polluting industries first. Regression analyses demonstrate that SMEs with a higher proportion of institutional investors are more willing to disclose content elements to satisfy greater stakeholder scrutiny. Few studies evaluate the level of alignment of IR content elements for SME context. This study constructs an index relating to the IR content elements and provides new insights into the evolution of the adoption of IR by SMEs. Additionally, the paper explores how SMEs create value through the content elements of the IIRC framework underlining the integrity issue. This paper enriches the emerging literature on the adaptation of IR in SMEs by examining the financial drivers for the disclosure of IR content elements. Turkish SMEs still have a long way to go, particularly in terms of the corporate governance principles disclosure. Insufficient disclosure of governance-related content elements could be of concern to policymakers, such as governance mechanisms, strategy, and allocation of resources.
Keywords: content analysis; integrated reporting; integrity; market value; SMEs; voluntary disclosures; QUALITY; MARKET; FIRM; DETERMINANTS; Social Sciences - Other Topics